Analysis of Tari Kelelawar Movement Variations Based on the Wordwall Game for 9th Grade at SMPN 7 Semarang - Nahla; Eny Kusumastuti (Gondang: Jurnal Seni dan Budaya, 2026)
This study aims to analyze the variations of Tari Kelelawar movements and test the use of the Wordwall educational game as a movement analysis medium in dance learning for 9th grade students at SMPN 7 Semarang. The method used is Research and Development (R&D) with the ADDIE development model which includes five stages, namely analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, documentation, and media feasibility testing to obtain comprehensive information regarding the characteristics of dance movements and the application of learning media. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing to ensure systematic and coherent interpretation. Based on the results of the media expert validation test, Wordwall was declared suitable for use with advantages in aspects of visual appearance, technical quality, and high interactivity. The implementation results showed that the average student response score reached 88% (very suitable category). The use of interactive features such as Match-Up, Labeled Diagram, Group Sort, and Open the Box also proved effective. These features help students deconstruct the complexity of movement visually and independently, while encouraging their active involvement during the learning process. This study concludes that Wordwalls can function effectively as a visual analysis medium to support dance movement analysis and enhance students' understanding of dance learning in a local cultural context.